2019
DOI: 10.1002/cphc.201900377
|View full text |Cite
|
Sign up to set email alerts
|

Phenol Tautomerization Catalyzed by Acid‐Base Pairs in Lewis Acidic Beta Zeolites: A Computational Study

Abstract: We investigate the tautomerization of phenol catalyzed by acid‐base active pair sites in Lewis acidic Beta zeolites by means of density functional calculations using the M06‐L functional. An analysis of the catalytic mechanism shows that hafnium on the Beta zeolite causes the strongest absorption of phenol compared to zirconium, tin, and germanium. This can be rationalized by the highest delocalization of electron density between the Lewis site and the oxygen of phenol which can in turn be quantified by the pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…These methods and basis sets have shown to be appropriate for metal clusters supported by zeolites in the literature. [44][45][46] All calculations were performed using the Gaussian 09 program. 47 In addition, non-covalent interaction (NCI) analysis was performed with the Multiwfn program 48,49 and visualized using the VMD program.…”
Section: Methodsmentioning
confidence: 99%
“…These methods and basis sets have shown to be appropriate for metal clusters supported by zeolites in the literature. [44][45][46] All calculations were performed using the Gaussian 09 program. 47 In addition, non-covalent interaction (NCI) analysis was performed with the Multiwfn program 48,49 and visualized using the VMD program.…”
Section: Methodsmentioning
confidence: 99%
“…[ 191 ] After further analysis, it was found that this reaction contained two steps, the dissociation of O‐H in phenol and the subsequent protonation of the intermediate, where the first one was the rate‐determining step. [ 192 ]…”
Section: Catalytic Applications Of Sn‐ and Zr‐zeolitesmentioning
confidence: 99%
“…[191] After further analysis, it was found that this reaction contained two steps, the dissociation of O-H in phenol and the subsequent protonation of the intermediate, where the first one was the rate-determining step. [192] N-alkylation reaction of aniline with benzyl alcohol was attempted over various silicates (MFI and Beta) with Sn, Ti, Zr, and Hf active sites. [22] Among these zeolites, Zr-Beta and Hf-Beta exhibited excellent activity and selectivity for this conversion.…”
Section: Other Reactionsmentioning
confidence: 99%